ANALISIS HASIL TES EVALUASI PENDIDIKAN PADA MAHASISWA DITINJAU DARI PERBEDAAN GENDER - Anik Kurniawati (Jurnal Ilmiah Didaktika, 2018)
Analysis of test results is one of the materials that must be mastered by students in educational evaluation courses. In this analysis students are also required to be able to make questions well and be able to evaluate them. The purpose of this study is to describe the results of the calculation of the scores that have been obtained from the evaluation data that has been carried out in terms of gender differences. The approach used is quantitative and qualitative approaches. The research subjects were IKIP Budi Utomo Malang students in the 2016 class B even semester 2017/2018. The instrument used in this study is a test question. From the calculation of the data obtained it can be seen that the percentage level of difficulty of male students is 32.84%, while for the calculation of the level of difficulty of female students is 42.95%. The percentage of differentiation for male students is 29.26%, and the percentage of female students is 38%. For the percentage of male students the answer pattern is 39.16%, while the percentage pattern of answers for female students is 51.59%. Based on the data it can be concluded that female students better understand the educational evaluation material which consists of the level of difficulty, the different power of the questions, and the answer pattern of the questions. It is expected that the education evaluation courses between male and female students have a balance in understanding the material and not only being dominated by female students. For further research can be developed how to design learning that is able to accommodate both reasoning and accuracy, so that between male and female students have the same opportunity to understand educational evaluation material.